Ethical education of health preservation in the muslim medical heritage: a comparative study of ethics of health conservation between Ibn Sina's Qanon and Razi's Hawi - Hashi, Abdurezak Abdulahi (2010)
Muhamed Ibn Zakariya Al-Razi (d.925) and Abu Ali Al-Husayn Ibn Abd. Allah Ibn Sina(d.1037), were among the early Muslim scientists whose contributions to natural sciences are well appreciated and acknowledged by modern scholars of both the western and the Muslim world. They were acknowledged not because they were instrumental to transfer the intellectual heritage of the ancient civilizations to the modern civilization, but they have pioneered the development of different scientific fields and methods of learning science, The framework to their knowledge quest includes medicine and surgery, pharmacy and pharmacology, engineering and technology, astronomy, mathematics and physics, chemistry and geography, botany and zoology, philosophy and ethics, arts and culture. Beside their enthusiastic interest in the natural and life science, the inquiry about the human factor in the application and appreciation of sciences, was never been overlooked. As such, despite their interest in scientific innovations and discovers, ethics and human morality remained an integral part of their scientific quest, particularly, in the application of science, such as medical science. Like other Muslim scientists, both Ibn Sina and Al-Razi have allocated a considerable portion of their attention to the importance and role of ethical education to the medical field, especially with the issues related to health preservation and disease prevention. In his monumental work on medicine (Al-Hawi), Al-Razi addresses the importance of ethical virtues in medical practices and health preservation. While in his encyclopedic work on medicine and health (Al-Qanun), Ibn Sina mentions the role of human behavior in the healthy protection. Through textual and analytical methods, this paper endeavors to study the ethical education of health conservation between Qanon of Ibn Sina and Hawi of Al-Razi. While exposing convergent and divergent points between these two works on the subject, this study also strives to examine their contemporary relevance and significance. Thus, this paper is made of two main segments; exposition of the ethical education of these two works related to the health preservation, and second, evaluation of such contents.